2010
DOI: 10.1038/pcan.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of statins to clinical presentation and biochemical outcomes after radical prostatectomy in Korean patients

Abstract: The aim of this study was to determine whether or not statins influence biochemical recurrence (BCR) in Korean patients undergoing surgical treatment for prostate cancer. We reviewed data from 687 men who underwent radical retropubic prostatectomy and who did not receive neoadjuvant treatment. Of these patients, 87 reported the use of preoperative statins at surgery. BCR-free survival was determined after exclusion of 78 patients with lymph node metastases and/or who received immediate adjuvant treatment. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
2
27
1
1
Order By: Relevance
“…Two papers reported more favorable pathologic characteristics [20,21]. Only one study found a dose-dependent reduction of the biochemical recurrence risk [22], while three others reported that there was no statistically significant association [11,20,23]. Ritch et al [24] had similar findings as our series.…”
Section: Discussionsupporting
confidence: 84%
“…Two papers reported more favorable pathologic characteristics [20,21]. Only one study found a dose-dependent reduction of the biochemical recurrence risk [22], while three others reported that there was no statistically significant association [11,20,23]. Ritch et al [24] had similar findings as our series.…”
Section: Discussionsupporting
confidence: 84%
“…22 We also excluded studies of statin use and PrCa recurrence in men who received another treatment option, eg radiation and/or hormones, or those that analyzed BCR and PrCa specific mortality together. 23,24 In the metaanalysis we included 5 studies that captured BCR in relation to statin use [12][13][14][15][16] as well as the results of the current study.…”
Section: Meta-analysis Of Studiesmentioning
confidence: 99%
“…11 Several groups have assessed the impact of statins on the BCR risk after ORRP and reported inconsistent findings. [12][13][14][15][16] The primary objective of the current study was to evaluate the effect of statin therapy on BCR in a large cohort of men who underwent ORRP, as done by a single surgeon, of whom all participated in a long-term prospective, longitudinal study. A second objective was to perform a meta-analysis of the effect of statins on BCR after ORRP using data from our institution and 5 peer reviewed, published studies.…”
mentioning
confidence: 99%
“…Prior studies suggest elevated serum cholesterol, a known CAD risk factor, may be associated with PCa risk and disease grade (4,5). Furthermore, several recent studies found statins, which benefit men with CAD, may reduce overall PCa risk and disease recurrence (6,7), though conflicting data exist (8). Only a few studies examined the relationship between CAD and PCa risk with mixed results (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%